SMT at the International Maritime Organization: Experiences with Combining In-house Corpora with Out-of-domain Corpora - Pouliquen, Bruno; Junczys-Dowmunt, Marcin; Pinero, Blanca; Ziemski, Michal (European Association for Machine Translation 2015, 2015)
This paper presents a machine translation tool – based on Moses – developed for the International Maritime Organization (IMO) for the automatic translation of documents from Spanish, French, Russian and Arabic to/from English. The main challenge lies in the insufficient size of in-house corpora (especially for Russian and Arabic). The United Nations (UN) granted IMO the right to use UN resources and we describe experiments and results we obtained with different translation model combination techniques. While BLEU results remain inconclusive for combinations, we also analyze user preferences for certain models (when choosing between IMO only or combined with UN). The combined models are perceived by translators as being much better for general texts while IMO only models seem better for technical texts.